REALIZING SUPERIOR AND PROFESSIONAL ENTREPRENEURSHIP: A SUSTAINABLE BUSINESS MODEL FOR ACHIEVING INCLUSIVE ECONOMIC GROWTH (AT THE INTERNATIONAL CONFERENCE OF LAMAPPAPOLEONRO UNIVERSITY) - Aulia Ananda; Rahmawati Rahmawati; Asnia Minarti; Shangrilla Malle; Reza Kurniawan; A. Zulkifli Nusri (Adisam Publisher, 2025)
This abstract was presented at the international conference of Lamappapoleonro University, themed “Excellent and Professional Entrepreneurship for Global Sustainability”, conducted via Zoom on October 13, 2025, at 1:30 PM. The speakers were scholars from several universities in India, Pakistan, Malaysia, Thailand, and Uzbekistan. This study aims to examine the role of superior and professional entrepreneurship in promoting inclusive economic growth through the application of the Sustainable Business Model (SBM). In today's global and digital economy, entrepreneurship no longer focuses solely on profit, but also on social and environmental impact, which is at the core of professionalism and excellence. This study analyzes how integrating sustainability principles into the business value chain can increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) and create economic opportunities for underrepresented groups. The method used was a systematic literature review and analysis, examining various successful models and strategies in promoting adaptive and innovative entrepreneurship. Key findings show that MBB, which includes aspects of good governance, environmentally friendly product or process innovation, and social value creation, significantly contributes to the economic resilience of MSMEs. In addition, the adoption of digital technology and ecosystem collaboration (involving the government, private sector, and civil society) has proven effective in overcoming access and literacy gaps, thereby strengthening the inclusiveness of economic growth. Professional entrepreneurship acts as an agent of change that not only generates economic value but also contributes to social and environmental well-being. Therefore, this study recommends targeted policy interventions to strengthen digital capacity, gender-sensitive training, and the development of regulations that support the full participation of entrepreneurs in realizing sustainable and equitable economic development.